The complete chloroplast genome of Vancouveria planipetala, with implication for the phylogeny of Ranunculales - Zhenyu Jin; Jocelyn M. Losh; Wenqing Ye; Pan Li (Mitochondrial DNA. Part B. Resources, 2018)
Vancouveria planipetala (Berberidaceae) is a perennial herb which has high ornamental and ecological values. In this study, we assembled the complete chloroplast (cp) genome of V. planipetala. The whole cp genome of V. planipetala is 156,871 bp in length, comprising a pair of inverted repeat (IR) regions (25,888 bp) separated by a large single copy (LSC) region (88,321 bp) and a small single copy (SSC) region (16,772 bp). The cp genome contains 114 unique genes, including 80 protein-coding genes, 30 tRNA, and four rRNA genes, with 17 genes duplicated in IRs. Phylogenetic analyses showed that Papaveraceae is the basal group of Ranunculales.